Transnational corporate elites in Japan: international career mobility in East and South Asia - Kwon, Jaok; Pohlmann, Markus; Schöttli, Jivanta (International journal of Japanese sociology, 2019)
Although mainstream globalization literature has attempted to provide an empirical proof of the rise of transnational business elites using several indicators, it is still not clear how to pinpoint transnationality and to establish whether globalization has led to the erosion of nation-state boundaries through worldwide mobility and networks, as globalization theorists argue. Using empirical data on career paths and mobility over three decades in Japan - compared with other East Asia economies and India - we examine the shift in career mobility. First, we maintain that a comprehensive understanding of social, political and cultural dimensions need to be considered in a discussion of transnationality. Second, we suggest that the globalizing economy does not necessarily lead to the weakening of the nation-state territory and its institutions in all sociocultural and political dimensions. In particular, transnationality in career mobility in Asian economies is not greatly evident. We propose instead that a new career pattern, which we call brain circulation, highlighting the importance of international experience, has emerged.